The association between symptomatic remission and social support in community-dwelling schizophrenia patients during COVID-19 - Yao, Lansicheng; Liu, Hongying; Pan, Qiuyu; Tian, Xiaobing (Frontiers in Psychiatry, 2024)
Schizophrenia is a severe and enduring psychiatric disorder, characterized by substantial challenges in achieving symptomatic remission. Up to now, there have been limited studies examining the association between remission status and social support in patients with schizophrenia during COVID-19. This study aimed to investigate the remission status of community-dwelling schizophrenia patients during the pandemic and explore whether symptomatic remission is significantly associated with social support in a cross-sectional study.727 schizophrenia patients were recruited using a cluster random sampling method in the local community. Face-to-face interviews were used to gather data on participants' clinical characteristics, sociodemographic, social support, and symptomatic remission criteria. Logistic regression models were deployed to identify potential relationships between symptomatic remission and social support. Among the 727 patients in our study, a substantial proportion of 522 (71.80%) achieved symptomatic remission, while 205 (28.2%) did not. Remarkably, those who achieved symptomatic remission exhibited a higher level of social support (28.32 ± 6.82) compared to those who did not. The proportion of patients achieving symptomatic remission in the low (19.4%), medium (46.2%), and high (34.3%) social support groups was 56.7%, 66.1%, and 88.0%, respectively. Moreover, the crude odds ratio for the association between social support and symptomatic remission was 3.20 (95% CI: 2.45-4.18). After controlling for all confounding factors, the adjusted odds ratio remained significant at 3.02 (95% CI: 2.30-3.97). This consistent association underscores the critical role of social support in influencing symptomatic remission among community-dwelling schizophrenia patients, especially during the COVID-19